2018
DOI: 10.18820/24150487/as25i1.2
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the causes, cost effects and solutions to design-errorinduced variations on selected building projects in Nigeria

Abstract: Design errors and variations are inherently part of many construction projects and require deliberate effort to combat. The literature reviewed indicates that empirical studies of the cost effect of design-error-induced variations are scarce. This study investigates the causes of variation on building projects, the frequent design errors that lead to variation, the effects of design error on variation cost, and solutions to design-error-induced variation in design documents. A mixed methods research (interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Sufficient time given to the designers and thorough reviewing of design details would assist in minimizing this problem. This result of the study was in agreement with previous study by Dosumu & Aigbavboa (2018) who found poor working drawing as the major cause of variation on selected building projects in Nigeria. "Inadequate project objectives" is also among the highly significant causes of variation orders as perceived by all respondents with the view that it may further add more complication to the realization of project objectives.…”
Section: Evaluation Of Key Causes Of Variation Orderssupporting
confidence: 92%
“…Sufficient time given to the designers and thorough reviewing of design details would assist in minimizing this problem. This result of the study was in agreement with previous study by Dosumu & Aigbavboa (2018) who found poor working drawing as the major cause of variation on selected building projects in Nigeria. "Inadequate project objectives" is also among the highly significant causes of variation orders as perceived by all respondents with the view that it may further add more complication to the realization of project objectives.…”
Section: Evaluation Of Key Causes Of Variation Orderssupporting
confidence: 92%
“…This is due to the clarity of project plans, as well as the confidence of assumptions and design variables established early in the planning stage, which becomes increasingly apparent to the design team during construction [20]. Construction design changes have a huge effect on project performance; they are complex to tackle when the exact cause is unknown, although they can be managed, if not entirely reversed [21]. Alaryan et al [10] investigated the causes and effects of design change in construction projects in Kuwait and identified 20 unique items.…”
Section: Causes Of Design Changementioning
confidence: 99%
“…There are many existing publications dedicated to causes of profit losses and construction delays on international EPC mega projects: Asia [5][6][7][8][9][10][11][12][13][14][15][16], Europe [17,18], Africa [19][20][21][22], Americas [23][24][25], and Australia [26,27]. Among the factors identified, the most common cause of project schedule and cost overrun was found to be poor design development prior to construction [5][6][7][8]12,13,[15][16][17][18][22][23][24]27].…”
Section: Existing Literaturementioning
confidence: 99%
“…Sambasivan [6], Wong [27] and Habibi [23] hypothesized that design error and change is one of the major causes of delays through diverse data analysis techniques, such as a relative importance index ranking method, severe index, etc. Dosumu [22] indicated that about 36% of cost variation is caused by design errors, and recommended design maturity review prior to use to minimize design-error-induced variations. Many previous studies show data collection and analysis using a considerable amount of historical data.…”
Section: Existing Literaturementioning
confidence: 99%